PERANAN STRATEGIC PROCESSES DALAM PROSES INTERNASIONALISASI JASA PENDIDIKAN TINGGI DI INDONESIA - Budiprasetyo, Benedictus K (JURNAL BISNIS STRATEGI, 2007)
The implementation of the competitive advantage development in the resource based theory depends on the insideout, outsidein, and spanning process as a combination of strategic actions. Hence, this empirical research explores how the customer cultural awareness and knowledge management development as the insideout processes and the market characteristic as the outsidein process influence the management behavior of the higher education institution and the implementation of the internationalization strategy as the spanning process. Using the data form questionnaire filled by the Indonesian higher education management processed with PLS model estimation, it founded that the insideout process influence the spanning process. The results shows that the insideout processes significantly influence the spanning process with cultural awareness OSE .33, knowledge management OSE .37, and the R2 .42. The management behavior significantly influence (OSE:.45 and R2:.30) tne internationalization strategy implementation. This research result was a new phenomenon, since theoretical propose a significant influence both of insideout and insideout processes to the spanning process, but the result was consistent to the RBV context that the insideout process is the main consideration of the internationalization process. This research result has its implication that the intematicnalization process of Indonesian higher ecuceuon institution in the context of insideout process influence to (he spanning process as a serial of strategic processes.